Pathogenicity and Control of Phomopsissp. Associated with Yam Rot Using Bark Extracts of Mangifera indica L. and Parinari polyandra Benth - Ahmed, O.; Baba, H.S.; Yusuf, S.Y.; Lawal, R.A.; Adebayo, O.V.; Ojomu, J.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
The antifungal property of Mangifera indica and Parinari polyandra bark extracts against Phomopsis sp. isolated from rotting yam tubers was evaluated. Stock solutions prepared by dissolving 1 g of each extract in 100 ml of sterile water (i.e. 1% w/v) was applied at 1:2, 1:4 and 1:6 (i.e. 1 part of the stock to 2, 4 and 6 parts of the culture medium v/v) in-vitro. The extracts were later applied at 0.5%, 1% and 1.5% w/v as coating on the yam tubers. The plant extracts significantly suppressed the growth of the fungus in vitro and reduced rot development in healthy yam tubers. The percentage inhibition of growth of the test fungus on medium treated with Parinari polyandra bark extract ranged between 10.50 – 21.35 , 19.52 – 43.15 , 29.41 – 50.14 , 33.18 – 51.92 and 27.71 – 47.30 for concentration range between 1:6v/v – 1:2v/v of the stock solution at days 3 , 5 , 7 , 9 and 11 of plating respectively. Percentage inhibition of growth of the fungus on Mangifera indica extract treated medium also ranged between 11.02 – 39.06, 34.93 – 49.32, 34.45 – 52.94, 38.37 – 54.18 and 31.88 – 50.42 for the same concentration range and days after plating respectively. The study showed the potentials of these plant extracts in the control of post harvest rots of yam tubers.